2008
DOI: 10.1162/pres.17.6.575
|View full text |Cite
|
Sign up to set email alerts
|

The Comparisons of Heart Rate Variability and Perceived Exertion During Simulated Cycling with Various Viewing Devices

Abstract: Sympathovagal modulation during immersion in a virtual environment is an important influence on human performance of a task. The aim of this study is to investigate sympathovagal modulation using heart rate variability and perceived exertion during exercise in a virtual reality (VR) environment.Sixteen young healthy volunteers were tested while using a stationary bicycle and maintained at an anaerobic threshold intensity for exercise sessions of approximately 10 min duration. Four randomized viewing alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The lack of correlation between VLF and EDA reactivity suggests that VLF does not represent sympathetic cardiac modulation as suggested recently by a number of papers [2, 31-34]. This contradicts the paper by Shaffer et al [2] which suggests that the amplitude and frequency of the VLF rhythm is modulated by efferent sympathetic activity.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The lack of correlation between VLF and EDA reactivity suggests that VLF does not represent sympathetic cardiac modulation as suggested recently by a number of papers [2, 31-34]. This contradicts the paper by Shaffer et al [2] which suggests that the amplitude and frequency of the VLF rhythm is modulated by efferent sympathetic activity.…”
Section: Discussionmentioning
confidence: 78%
“…However, a relatively recent study has suggested that the VLF rhythm is intrinsically generated by the heart and that the amplitude and frequency of these oscillations are modulated by efferent sympathetic activity [2]. Therefore, some studies have actually utilized VLF power as a reflection of sympathetic tone [2, 31-34]. …”
Section: Introductionmentioning
confidence: 99%
“…However, until recently, very few studies examined whether VR stationary exercise bike equipment truly promotes a dissociation attentional focus and enhances enjoyment of the experience. Indeed, few studies have directly tested the effect of a VR setting on affective states and/or performance during indoor cycling (Annesi & Mazas, 1997;Chuang et al, 2003;Huang, Tsai, Sung, Lin, & Chuang, 2008;IJsselsteijn, De Kort, Westerink, De Jaggerand, & Bonants, 2006;Mac Rae, Miller-Perrinand, & Tinberg, 2003;Plante, Aldridge, Ogden, & Hanelin, 2003;Plante, Frazier, et al, 2003). Annesi and Mazas (1997) tested the effect of a 14-week VR exercise bicycle program in a fitness center on adherence and exercise-induced feeling states among 45 adults, aged between 20 and 60 years.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, few studies have directly tested VR effects on exercise performance. Indeed, in a recent paper Huang et al (2008) report that VR feedback actually enables anaerobic exercise for longer duration by reducing perceived exertion (see also Chuang et al, 2003). However, these two studies were conducted in a rehabilitation (poststroke) context that may not be easily generalized to nonpathologic populations.…”
Section: Introductionmentioning
confidence: 99%
“…An initial demonstration of the interest of such measures was made with the famous "pit room" experiment [24]. Recent studies [25] have proposed to use heart rate variability, instead of average heart rate, to measure relaxation effects of immersive displays on exertion during a fitness task. This type of measurement of presence is now widely used, often in conjunction with subjective (questionnaire) evaluations.…”
Section: Physiological Measuresmentioning
confidence: 99%